2022
DOI: 10.48550/arxiv.2205.08884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active galactic nuclei jets simulated with smoothed particle hydrodynamics

Abstract: Active galactic nuclei (AGN) jets play an important role as a feedback mechanism that quenches the growth of massive galaxies. These jets have so far been simulated almost exclusively with grid-based codes. In this work we present results from hydrodynamical tests of AGN jets simulated with the SWIFT code and its implementation of smoothed particle hydrodynamics (SPH). We reach numerical resolutions of more than a million particles per jet, unprecedented for an SPH code. In all cases we find broad agreement be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…In deriving equation ( 7), Lubow et al ( 2002 ) considered the case of a nearly Keplerian disc with a weak tilt. Despite these assumptions, observations have found that bending wave radii given by equation ( 8) are able to explain quasi-periodic oscillations in light curves of X-ray binaries thought to host hot accretion flows (Ingram, Done & Fragile 2009 ;Ingram & Done 2012 ). In addition, simulations have reproduced the findings from Lubow et al ( 2002) (e.g.…”
Section: The Structure Of the Disc: Bending Wave Regimementioning
confidence: 99%
“…In deriving equation ( 7), Lubow et al ( 2002 ) considered the case of a nearly Keplerian disc with a weak tilt. Despite these assumptions, observations have found that bending wave radii given by equation ( 8) are able to explain quasi-periodic oscillations in light curves of X-ray binaries thought to host hot accretion flows (Ingram, Done & Fragile 2009 ;Ingram & Done 2012 ). In addition, simulations have reproduced the findings from Lubow et al ( 2002) (e.g.…”
Section: The Structure Of the Disc: Bending Wave Regimementioning
confidence: 99%
“…Yet many important questions remain unanswered. Jet activity is intermittent (Schoenmakers et al 2000;Best et al 2005;Sabater et al 2019;Jurlin et al 2020;Quici et al 2021), but the mechanisms responsible for this modulation are unknown; plausible candidates include magnetically arrested accretion (Bisnovatyi-Kogan & Ruzmaikin 1974;Tchekhovskoy et al 2011;Tchekhovskoy & McKinney 2012), chaotic cold accretion (Gaspari et al 2017;McKinley et al 2022), and jet-mediated feedback (Bourne & Sijacki 2021;Huško & Lacey 2022). Similarly, while some studies (e.g.…”
Section: Introductionmentioning
confidence: 99%